2006
DOI: 10.1016/j.ajog.2005.10.817
|View full text |Cite
|
Sign up to set email alerts
|

Is planned vaginal delivery for breech presentation at term still an option? Results of an observational prospective survey in France and Belgium

Abstract: Objective: A large trial published in 2000 concluded that planned vaginal delivery of term breech births is associated with high neonatal risks. Because the obstetric practices in that study differed from those in countries where planned vaginal delivery is still common, we conducted an observational prospective study to describe neonatal outcome according to the planned mode of delivery for term breech births in 2 such countries. Study design: Observational prospective study with an intent-to-treat analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
290
5
56

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(366 citation statements)
references
References 24 publications
15
290
5
56
Order By: Relevance
“…Similar results have been reported by other authors [10][11][12]. The rate observed in this study is higher than the rates observed in the other series [8].…”
Section: Discussioncontrasting
confidence: 51%
“…Similar results have been reported by other authors [10][11][12]. The rate observed in this study is higher than the rates observed in the other series [8].…”
Section: Discussioncontrasting
confidence: 51%
“…3 This position, usually maintained for days or weeks after delivery, may affect gait and motor function up to the age of 12 to 18 months. 2 Previous reports have shown that lack of motion leads to a decrease in bone mineral density. 4 Using the mechanostat model, Frost et al 5 established the importance of mechanical loading in the development and maintenance of bone health.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These fetuses usually have a limited motion of their lower limbs during the last weeks of gestation. 3 Being crammed in utero, these fetuses often adopt abnormal position such as extreme hips flexion and/or knees hyperextension.…”
Section: Introductionmentioning
confidence: 99%
“…10 The PREMODA trial which is often referred to as the "antidote to the Term Breech Trial" was conducted in France and Belgium. They used the same criteria and outcome measures as the Term Breech Trial (TBT), except the decision for a Caesarean Section (CS) or Vaginal Breech Birth (VBB) was the woman"s, not randomized.…”
Section: Discussionmentioning
confidence: 99%